Peningkatan Pengetahuan Kesehatan Gigi dan Mulut Anak di Dusun Botokan, Sendangrejo, Minggir, Sleman - Urmila Syifa Kurniawan; Nevlein Syavira Akmalia; Naufal Hanif Syah Novildan; Dwi Aji Nugroho; Sartika Puspita (Dental Agromedis, 2023)
Public awareness of dental and oral health in Indonesia is still very low, which can be measured by the number of people who go to the dentist when they have problems with their teeth and mouth. The purpose of this activity was to increase knowledge about dental and oral health in children to prevent increasing dental and oral health problems in Dusun Botokan, Desa Sendangrejo. This community service method consisted of four stages of activity, namely on the first day counseling on Clean and Healthy Behavior (PHBS), then on the 2nd day the practice of PHBS was carried out which was explained on the first day. On the 3rd activity, there was counseling on Dental and Oral Health, then on the 4th day, Dental and Oral Health practices were carried out and distribution of free toothbrushes and toothpaste. The results of this service showed an increase in children's knowledge about clean and healthy living behavior by 58% and knowledge of maintaining oral hygiene by 52% and there was an increase in brushing teeth and hand washing skills by 100% (31 children).Keywords: dental and oral health; PHBS; preventive